2006
DOI: 10.1007/s11010-006-0720-4
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of topical propolis on experimental keratitis via nitric oxide levels in rabbits

Abstract: The aim of this study was to investigate antioxidant, anti-inflammatory, and antibacterial properties of propolis in the treatment of experimental Staphylococcus aureus keratitis. Twenty young New Zealand white rabbits were used in this experiment. Staphylococcus aureus were given by intrastromal injection to 16 rabbits and 4 rabbits were used as control group (Group 1). Group 2 was treated with phosphate-buffered solution drops; Group 3 was administered ethanolic extract of propolis drops; Group 4 received to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Numerous studies have showed various pharmacological activities such as antibacterial, antifungal, antiviral, antiprotozoal anti-inflammatory, hepatoprotective, antioxidant, antitumor, etc. (Banskota et al 2001;Duran et al 2006;Oksuz et al 2005;Onlen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have showed various pharmacological activities such as antibacterial, antifungal, antiviral, antiprotozoal anti-inflammatory, hepatoprotective, antioxidant, antitumor, etc. (Banskota et al 2001;Duran et al 2006;Oksuz et al 2005;Onlen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various biological properties have been demonstrated and attributed to different types of propolis, including antibacterial, antifungal, antiprotozoal, antioxidant, antitumor, anti-infl ammatory, anesthetic, wound healing, immunomodulatory, antiproliferative and anticariogenic activities (Dobrowolski et al, 1991;Ivanovska et al, 1995;Moura et al, 1999;Kujumgiev et al, 1999;Isla et al, 2001;Chen et al, 2004;Simões et al, 2004;Duran et al, 2006;Medic-Saric et al, 2009;Araujo et al, 2010;Sforcin, 2007;Libério et al, 2009;Pagliarone et al, 2009, Paulino et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products play a highly significant role in new agents searching for the treatment of various diseases (Duran et al 2006;Oksuz et al 2005;Allahverdiyev et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Propolis is a useful substance in medicine. In the literature, propolis has various pharmacological activities such as antiparasitic (Duran et al 2008), antibacterial (Onlen et al 2007a, b;Duran et al 2006;Oksuz et al 2005;Onlen et al 2007a, b), antifungal (Siqueira et al 2009), antiviral (Shimizu et al 2008), antiinflammatory (McLennan et al 2008, immunostimulatory (Cuesta et al 2005), and anti-carcinogenetic activities (Diaz-Carballo et al 2008).…”
Section: Introductionmentioning
confidence: 99%